Initial Dosage Recommendation for Sirolimus in Children With Tuberous Sclerosis Complex - Wang, Dong-Dong; Chen, Xiao; Xu, Hong; Li, Zhi-Ping (Frontiers in Pharmacology, 2020)
Sirolimus is already used in the treatment of tuberous sclerosis complex (TSC), however, with narrow therapeutic range and considerable inter- and intra-individual pharmacokinetic variability, making it hard to develop a appropriate sirolimus initial dosage regimen, especially in children with TSC. The aim of this study was to recommend the optimal sirolimus initial dosing regimen in pediatric patients with TSC. Underlying physiological and genetic factors were collected to explore the effects on clinical sirolimus concentrations by establishing a nonlinear mixed effect (NONMEM) model, and to furtherly simulate the optimal sirolimus initial dosing regimen using Monte Carlo method in pediatric patients with TSC. The once-daily regimen and the twice-daily regimen were recommended, respectively. For once-daily regimen, the dosages of 0.10, 0.07, 0.05, 0.04, 0.03mg/kg/day were recommended for children with weight of 5-10, 10-20, 20-30, 30-50, and 50-60kg, respectively. For twice-daily regimen, the dosages of 0.04, 0.03, 0.02mg/kg/day (the daily dose was divided evenly into two doses) were recommended for children with weight of 5-20, 20-40, 40-60kg, respectively. The initial dosages of sirolimus in children with TSC were recommended for the first time.